Remaining Service Life Struktur Conveyor A pada Tambang Tambang Batubara PT XYZ di Kabupaten Banjar, Provinsi Kalimantan Selatan - Fajar Arifianto; Elfida Moralista; Zaenal (UNISBA Press, 2022)
Abstract. Conveyor is one of the tools used to move excavated materials such as coal. The conveyor structure used is made of carbon steel. Conveyor structures can experience a decrease in quality due to corrosion. This study aims to determine the type of corrosion, corrosion control, and remaining service life of the conveyor structure. In this study, observations of environmental conditions include an average rainfall of 217.53 mm/year, an average air temperature of 27.22 ⁰C, and average relative humidity of 83.48%. The actual thickness measurement of the conveyor structure is carried out using the Ultrasonic Thickness GaugeTT 130 at 25 test points. The methodology used is by measuring the thickness reduction of the conveyor structure due to corrosion to determine the corrosion rate and remaining service life of the conveyor structure. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method applied is the coating method with a 3-layer system including the primary coating using Seaguard 5000, intermediate coating using Sherglass FF, and top coating using Aliphatic Acrylic Modified Polyurethane. The corrosion rate on the conveyor structure is 0.1733 – 0.3133 mm/year. Based on the table, the relative corrosion resistance of steel is in a good category. Remaining Service Life of the conveyor structure is 7.56 – 11.86 years. There are 8 or 32% of test points that are estimated to not reach the design life of the conveyor structure (15 years). Abstrak. Conveyor merupakan salah satu alat yang digunakan untuk memindahkan material bahan galian seperti batubara. Struktur conveyor yang digunakan berbahan dasar baja karbon. Struktur conveyor dapat mengalami penurunan kualitas yang diakibatkan oleh korosi. Penelitian ini bertujuan untuk mengetahui jenis korosi, pengendalian korosi dan remaining service life struktur conveyor. Pada penelitian ini, pengamatan kondisi lingkungan meliputi curah hujan rata-rata 217,53 mm/tahun, temperatur udara rata-rata 27,22 ⁰C dan kelembapan relatif rata-rata 83,48 %. Pengukuran tebal aktual struktur conveyor dilakukan dengan menggunakan alat Ultrasonic Thickness GaugeTT 130 pada 25 test point. Metodologi yang digunakan yaitu dengan pengukuran pengurangan ketebalan struktur conveyor akibat korosi untuk menentukan corrosion rate dan remaining service life struktur conveyor. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Metode pengendalian korosi yang diaplikasikan yaitu metode coating dengan sistem 3 layer meliputi primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF dan top coating menggunakan Aliphatic Acrylic Modified Polyurethane. Corrosion rate pada struktur conveyor yaitu 0,1733 – 0,3133 mm/tahun. Berdasarkan tabel ketahanan korosi relatif baja termasuk ke dalam kategori good. Remaining Service Life struktur conveyor yaitu 7,56 – 11,86 tahun. Terdapat 8 atau 32% test point yang diperkirakan tidak dapat mencapai umur desain struktur conveyor (15 tahun).